Analysis of the Core Genome and Pan-Genome of Autotrophic Acetogenic Bacteria - Shin, Jongoh; Song, Yoseb; Jeong, Yujin; Cho, Byung-Kwan (Frontiers in Microbiology, 2016)
Acetogens are obligate anaerobic bacteria capable of reducing carbon dioxide (CO2) to multicarbon compounds coupled to the oxidation of inorganic substrates, such as hydrogen (H2) or carbon monoxide (CO), via the Wood-Ljungdahl pathway. Owing to the metabolic capability of CO2 fixation, much attention has been focused on understanding the unique pathways associated with acetogens, particularly their metabolic coupling of CO2 fixation to energy conservation. Most known acetogens are phylogenetically and metabolically diverse bacteria present in 23 different bacterial genera. With the increased volume of available genome information, acetogenic bacterial genomes can be analyzed by comparative genome analysis. Even with the genetic diversity that exists among acetogens, the Wood-Ljungdahl pathway, a central metabolic pathway, and cofactor biosynthetic pathways are highly conserved for autotrophic growth. Additionally, comparative genome analysis revealed that most genes in the acetogen-specific core genome were associated with the Wood-Ljungdahl pathway. The conserved enzymes and those predicted as missing can provide insight into biological differences between acetogens and allow for the discovery of promising candidates for industrial applications.